2017
DOI: 10.1016/j.molp.2016.11.001
|View full text |Cite
|
Sign up to set email alerts
|

An Arabidopsis ABC Transporter Mediates Phosphate Deficiency-Induced Remodeling of Root Architecture by Modulating Iron Homeostasis in Roots

Abstract: The remodeling of root architecture is a major developmental response of plants to phosphate (Pi) deficiency and is thought to enhance a plant's ability to forage for the available Pi in topsoil. The underlying mechanism controlling this response, however, is poorly understood. In this study, we identified an Arabidopsis mutant, hps10 (hypersensitive to Pi starvation 10), which is morphologically normal under Pi sufficient condition but shows increased inhibition of primary root growth and enhanced production … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
108
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 131 publications
(109 citation statements)
references
References 55 publications
1
108
0
Order By: Relevance
“…Although NRAT1, a member of the Nramp transporter family, has been shown to mediate Al transport in rice (Xia et al ., ; Li et al ., ), there is as yet no evidence for the existence of an Nrat1 functional ortholog in Arabidopsis . By contrast, ALS1 and ALS3, two proteins encoding half‐ABC type transporters, have frequently been suggested to be involved in mediating Al sequestration into Arabidopsis vacuoles (Larsen et al ., , ), although more recently they have been associated with modulating phosphate and iron homeostasis (Belal et al ., ; Dong et al ., ). In the present study, neither ALS1 nor ALS3 transcriptional differences were observed between WT and cbl1 , thereby emphasizing the notion that the Al‐hypersensitivity experienced by cbl1 does not result solely from an increase in Al uptake.…”
Section: Resultsmentioning
confidence: 97%
“…Although NRAT1, a member of the Nramp transporter family, has been shown to mediate Al transport in rice (Xia et al ., ; Li et al ., ), there is as yet no evidence for the existence of an Nrat1 functional ortholog in Arabidopsis . By contrast, ALS1 and ALS3, two proteins encoding half‐ABC type transporters, have frequently been suggested to be involved in mediating Al sequestration into Arabidopsis vacuoles (Larsen et al ., , ), although more recently they have been associated with modulating phosphate and iron homeostasis (Belal et al ., ; Dong et al ., ). In the present study, neither ALS1 nor ALS3 transcriptional differences were observed between WT and cbl1 , thereby emphasizing the notion that the Al‐hypersensitivity experienced by cbl1 does not result solely from an increase in Al uptake.…”
Section: Resultsmentioning
confidence: 97%
“…17 NRGs involved in the biosynthesis of cellular amines and poly amines, are found to play a crucial role in different signaling networks and metabolic process of plants (Hussain et al, 2011; Berkowitz et al, 2016). Five NRGs which are involved in the movement of inorganic anions i.e., in or out of the cell or within a cell, or between plant cells are being observed as transporters which indicates their important functions during P, N, and K deficiency (Sharma, 2016; Dong et al, 2017; Forieri et al, 2017). Forty NRGs are participating in response to stress and stimulus indicates their involvement in different metabolic and signaling pathways.…”
Section: Discussionmentioning
confidence: 99%
“…To date, several mutants specifically altered in the local root response have been isolated561415161718, but only a few corresponding mutated genes have been identified. Much has been learned from LOW PHOSPHATE ROOT 1 (LPR1) and PHOSPHATE DEFICIENCY RESPONSE 2 (PDR2) , which genetically interact and are expressed in cell type-specific but overlapping domains of the root apex, comprising the RAM and early EZ8912.…”
mentioning
confidence: 99%